The role of group 3 innate lymphoid cell in intestinal disease - Li, Minghui; Wang, Zehui; Jiang, Wei; Lu, Yihan; Zhang, Jun (Frontiers in Immunology, 2023)
Group 3 innate lymphocytes (ILC3s), a novel subpopulation of lymphocytes enriched in the intestinal mucosa, are currently considered as key sentinels in maintaining intestinal immune homeostasis. ILC3s can secrete a series of cytokines such as IL-22 to eliminate intestinal luminal antigens, promote epithelial tissue repair and mucosal barrier integrity, and regulate intestinal immunity by integrating multiple signals from the environment and the host. However, ILC3 dysfunction may be associated with the development and progression of various diseases in the gut. Therefore, in this review, we will discuss the role of ILC3 in intestinal diseases such as enteric infectious diseases, intestinal inflammation, and tumors, with a focus on recent research advances and discoveries to explore potential therapeutic targets.